The role of cannabis clinics in the health system: a qualitative study of physicians' views in New Zealand - Withanarachchie V; Rychert M; Wilkins C (BioMed Central Ltd, 2023)
Background Privately-owned cannabis clinics have sprung up in many jurisdictions where medicinal cannabis has been legalised and provide an alternative pathway for patients who are unable or unwilling to access a prescription for cannabis-based medicinal products from their usual healthcare providers. Aims This study aimed to explore physicians’ views on cannabis clinics, including their perceptions of the role cannabis clinics play in the wider health system. Methods A qualitative study using in-depth, semi-structured interviews with thirty-one physicians affiliated with private and community clinics in New Zealand (including cannabis clinicians, GPs, and specialist doctors). The interviews were conducted from July to December 2021. Data were transcribed and analysed using inductive thematic analysis. Results Cannabis clinicians positioned themselves as (1) “service providers”, facilitating consumer access to cannabis prescriptions and products, and (2) “educators”, providing advice to patients and the wider physician community. While general practitioners and specialists recognised the benefits of specialised cannabis clinics (i.e., knowledge of products and a non-judgmental environment), they questioned the limited evidence of clinical efficacy for cannabis, potential financial conflicts of interests of cannabis clinicians that may blur their clinical judgement, and the risk of compartmentalising patients’ healthcare. Conclusions Our paper raises a number of challenges with attempting to integrate cannabis clinics into the wider health system.
© The Author(s) 2023
Keywords: CBD; Cannabidiol; Cannabis; Cannabis clinic; Medical marijuana; Medicinal cannabis; Qualitative research; Humans; Cannabis; New Zealand; Attitude of Health Personnel; General Practitioners; Medical Marijuana